2022
DOI: 10.1186/s40900-022-00404-3
|View full text |Cite
|
Sign up to set email alerts
|

A Blueprint for Involvement: Reflections of lived experience co-researchers and academic researchers on working collaboratively

Abstract: Patient and public involvement in health research is important to ensure that research remains relevant to the patient groups it intends to benefit. The UK NIHR funded Blueprint study aimed to develop a ‘model’ of effective service design for children and young people with common mental health problems. To ensure Blueprint’s findings were rooted in lived experience and informed by different perspectives, six young adults with lived experience of mental health issues were recruited, trained and employed as co-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…However, we learned that it was important to clarify roles and take time to explain the background and aims of the project at the beginning, particularly as it was recognised that these aims were ambitious. Similar to previous observations [ 50 ], adapting to the needs of individual public contributors was important and we identified that smaller group sessions outside the main TFGs was extremely valuable for some participants. In a systematic review of patient engagement in research, Domecq et al [ 1 ] also identified that spending adequate time to build reciprocal relationships between public contributors and researchers, fostering mutual respect and being clear on what is expected of public contributors were seen as important.…”
Section: Discussionsupporting
confidence: 86%
“…However, we learned that it was important to clarify roles and take time to explain the background and aims of the project at the beginning, particularly as it was recognised that these aims were ambitious. Similar to previous observations [ 50 ], adapting to the needs of individual public contributors was important and we identified that smaller group sessions outside the main TFGs was extremely valuable for some participants. In a systematic review of patient engagement in research, Domecq et al [ 1 ] also identified that spending adequate time to build reciprocal relationships between public contributors and researchers, fostering mutual respect and being clear on what is expected of public contributors were seen as important.…”
Section: Discussionsupporting
confidence: 86%
“…Their interpretations of the data were informed not only by their lived experience of mental illness but also by their lived experience of being a young person. We have published a paper where we discuss our reflections on co-research and provide guidance for other researchers on how to enable and support co-researcher involvement [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…More directly, our analysis highlights a need for those working with adolescent girls to create supportive, open spaces for nuanced conversations about the challenges they face, together with opportunities to bolster self-esteem and coping capacities. In research, policy, and practice, efforts to progress the agenda to improve girls' mental health can be best achieved through engagement with girls as key contributors to decision-making, as has been a key strength in our study; see, for instance, guidance and publications around conceptualising and reporting on co-produced health interventions and services [58,59].…”
Section: Discussionmentioning
confidence: 99%